PENGARUH PEMBERDAYAAN KARYAWAN DAN KOTMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. MUTIARA MUKTI FARMA - Simanjuntak, Diana Kristina; Siagian, Nalom; Sinaga, Kepler (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to measure the influence of employee empowerment and organizational commitment on employee performance at PT Mutiara Mukti Farma. The variables of this study are Employee Empowerment (X1) and Organizational Commitment (X2) to Employee Performance (Y). This study uses a type of survey research, with a quantitative research method. The sample of this study is employees working at PT Mutiara Mukti Farma with a total of 78 people. Data collection techniques by distributing questionnaires to employees. Then the data was analyzed by validity and reality test, regression test, normality test, multicollinearity and heterogeneity test, F test and T test using the SPSS 27 application. Based on the results of this study, it is concluded that Empowerment and organizational commitment have a positive and significant effect on employee performance. This is shown by the t-count value (14.533) in the empowerment variable, (3.599) in the organizational commitment variable and the t-value in the table of (1.665) this shows that the t-count value > the table and the significant value < 0.05. The result of F is calculated as (111.513) and the value of Ftable is (3.12) and significant is 0.000 < 0.05. The results of the Determination coefficient test were obtained at 0.695 which means that it is positively related to the dependent variable, Suggestions for companies that PT. Mutiara Mukti Farma can implement a more systematic and structured employee empowerment program. This can include skills training, greater delegation of responsibilities, and giving employees greater access to the resources and information they need to succeed in their jobs